Young Farmers’ Knowledge And Technical Practice On Developing Agribusiness Based On Parents’ Occupation - Diah Fitria Widhiningsih (Agro Ekonomi, 2019)
In family, parents act as facilitator who assist their children towards success. It can be seen in farm family while parents are taking part in decision making or giving suggestion on when to start planting crops. However, it is doubtful whether young farmers from non-farm family will experience the same opportunity. Therefore, this research aimed at understanding the different characters of young farmers whose parents work as farmers and non-farmers including their knowledge and technical practice on on-farm activity. This quantitative study was conducted in Prambanan and Kalasan Subdistrict, Sleman, D.I. Yogyakarta.  Selected through census, 42 young farmers were interviewed based on questionnaire. The data were analysed by using non-parametric analysis because of the data normality and Kolmogorov Smirnov’s analysis was implemented due to the objectives of this study. The result of analysis indicates that young farmers’ knowledge from different family background is also different. Young farmers from farm family have high knowledge on local wisdom in their organic farming. Furthermore, they are also socialized with more social networks. Their applied knowledge is better due to their experience and facility support. On the other hand, both young farmers who come from farm family and non-farm family do not perform different behaviour on their on-farm practice. New media including social media and social learning appear as the main additional support besides parents which can minimize the gap of practical skills among them. Collaboration on farmer group and extension workers’ role can be an alternative to develop young farmers’ knowledge and skills.